Peningkatan literasi dan numerasi dengan pendekatan interaktif dan komunikatif melalui program kampus mengajar di SD Negeri 15 Kota Bengkulu - Saputri, Rizky; Riswanto, Riswanto; Kurniawati, Juliana (Nur Science Institute, 2024)
The Teaching Campus Program is a program from the Ministry of Education and Culture that provides students with the opportunity to study outside campus and experience teaching at assigned schools. The background to this program is the low level of literacy and numeracy in Indonesia, which encourages interventions to improve the quality of elementary, middle school and vocational school education (excluding SMK PK). One of the targets of this program is SD Negeri 15 Bengkulu City. Technology adaptation is an important focus considering the rapid development of technology and the needs of students in the era of society 5.0. This program aims to increase student literacy and numeracy, introduce and utilize technology in the teaching and learning process, and enrich the learning environment through various work program initiatives. The methods used include planning, implementation and ongoing evaluation according to student abilities. The results of this program are expected to significantly improve students' literacy and numeracy skills, increase technology awareness and skills and create a more interactive and enjoyable learning environment. The implication of this program is to provide valuable practical experience for students, improve professional abilities and contribute directly to improving the quality of education in the program's target schools.